Organizational Effect on the Implementation of “SIMRS” (Hospital Management Information Systems) in Hospital: A Systematic Review - Windari, Adhani; Kismartini, Kismartini; Luqman, Yanuar; Wijanarko, Bagoes (Journal of Health Policy and Management, 2023)
Background: Utilization of information and communication technology has penetrated the field of health services. The form of health service innovation by utilizing information technology is the Hospital Management Information System (SIMRS). SIMRS is needed by Hospitals to ensure fast, accurate and reliable information needs in decision making, as well as the need for systematic data processing for strategic decision making. This study aimed to systematically review the influence of the organization on the implementation of “SIMRS”.Subjects and Method: A systematic review were conducted by searching articles from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles are “Organization” OR “group” AND “Hospital Management Information Systems” OR “SIMRS” or “Management” AND “Hospital” or “Healthcare”. Articles included are full-text English from 2014 to 2019. Articles were selected using a PRISMA flow diagram method.Results: Organizational factors which include organizational structure and organizational environment are the main determining factors in the implementation of information systems. The successful implementation of SIMRS from the aspect of organizational structure, namely the role of leaders in providing support, motivation to users, a supportive work culture and work environment, a clear division of tasks and authority, regular monitoring and evaluation activities, fulfillment of infrastructure needs that support the implementation of SIMRS, availability of budget allocations for training and competency development for system users. While the organizational environment aspect, namely the role of Hospital management, has established policies as guidelines for the implementation of SIMRS.Conclusion: Organizational factors from the aspect of organizational structure and organi-zational environment can increase the success of the implementation of "SIMRS" in Hospitals.Keywords: SIMRS, organizational structure, organizational environment.Correspondence: Adhani Windari. Doctoral Program in Public Administration Science, Universitas Diponegoro. Jl. Pleburan, South Semarang, 50241 Central Java. Email: adhaniwindari@student.-undip.ac.id. Mobile: +62 8170582584.Journal of Health Policy and Management (2023), 08(01): 13-22https://doi.org/10.26911/thejhpm.2023.08.01.02